Development of a New Salt of Piperine with Toluene Sulfonic Acid and Its Anti-Inflammation Effect In Vivo - Ilma Nugrahani; Ari Sartinah; Hidehiro Uekusa; Yuto Abekura; Slamet Ibrahim; Kusnandar Anggadiredja (Molecules)
Piperine (PPN) is a natural compound with an anti-inflammation effect and low solubility. Hence, some molecular modifications have improved its solid-state character, including cocrystal formation. However, the salt structure has yet to be widely studied. In this research, PPN was reacted with toluene sulfonic acid (TSA), which was expected to increase its solubility and anti-inflammatory effects. This experiment used solid-state reactions and analysis, including thermal analysis, infrared spectroscopy, and powder X-ray diffractometry, to characterize the new multicomponent solid phase. Next, single crystal R-ray diffractometry was used to determine the final three-dimensional conformation structure. After that, the salt, which can be reproduced by wet grinding, was tested for improved stability and anti-inflammatory effects. As a result, the PPN–TSA multicomponent solid was confirmed as a solid salt with monoclinic packing, exhibiting better solubility and anti-inflammation effects. Thus, this new organic salt has the potential for further phytochemical compound development.